Preliminary geohazard assessment and investigation of Tibungco and Bunawan areas in Davao City - Lee, Aujefel Amor Y.; Villasencio, Ernani D.; Castillo, Lorel M. (2014)
The University of Southeastern Philippines (USeP) College of Engineering in partnership with Holcim Philippines Inc-Davao Plant, and the Mines and Geosciences Bureau-Davao Region conducted the geohazard assessment study in Tibungco and Bunawan, Davao City. The coastal lines and interior part of Barangays Tibungco and Bunawan where flooding in noted during heavy downpour were assessed. The study aimed to identify the specific areas in Tibungco and Bunawan prone to flooding and landslide. It likewise aimed to increase the level of awareness of the stakeholders on the impact of flooding. The results of the study helped the local authorities to include in their planning and mitigation program the specific puroks that were assessed to be geologically hazardous.
Keywords: Geohazard assessment; Landslide mapping; Flooding